Choice of paddy marketing channel and its impact: evidence from Indian farm households - A G Adeeth Cariappa; Manjisha Sinha (Agricultural Economics Research Review, 2023)
This study uses data from a nationally representative survey to identify the factors that determine farm households’ choice of paddy marketing channels and the impact of the choice on the price realized. Small landholders sell their produce predominantly in informal or traditional value chains. Multinomial treatment effect estimates with endogenous market channels indicate that small landholders are less aware of the government-set floor price (minimum support price) and they realize lower prices and earn lower incomes than farmers selling in mandis (regulated markets).